Eﬀect of regrowth age the ruminal degradation of pisonay (Erythrina sp.) in Andean valley of Abancay - Choque Durand, Hubert (2018)
Andean valley of Abancay is used the pisonay (Erythrina sp.) as green fodder to supplement in the dry season. It was evaluated the chemical composition, ruminal degradability and parameters ruminal kinetics of dry mater (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), hemicellulose (HEM) and cellulose (CEL) at 120 and 365 days regrowth of the pisonay. A 5-year Holstein dry cow was used, with a live weight of 600 kg and permanent ruminal cannula. Samples of 5 g of each age of regrowth / nylon bag were incubated at 0, 3, 6, 12, 24 and 48 hours. The parameters of the ruminal kinetics were determined using the RUMENAL procedure, SOLVER function. The nutritional composition at 120 days was higher in the CP, FDA and CEL and at 365 days the DM, NDF and HEM. DM, NDF and ADF at 120 days of regrowth were higher than 365 days in the degradable fraction and effective degradability (P≤0.05). CP at 120 days of regrowth was higher soluble fraction, degradation rate and effective degradability (P≤0.05). DM and HEM at 365 days of regrowth was higher soluble fraction (P≤0.05). Degradation rate DM, ADF and CEL for both ages was similar (P≥0.05). HEM and CEL at 120 days was higher in the degradable fraction (P≤0.05) and for both ages effective degradability was similar (P≥0.05).